2021
DOI: 10.1007/s00402-021-03917-w
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the proximal radius in children: management and results of 100 consecutive cases

Abstract: Introduction Pediatric radial neck and head fractures are rare, accounting for only 1% of all fractures in children. The aim of this study is to describe the management and results of the respective fracture types and different injury characteristics. Materials and methods This study performs a retrospective data analysis of 100 consecutive patients with a fracture of the proximal radius treated in a single high-volume pediatric trauma center. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…There was no statistically significant difference in complication rates between the TEN and K wire groups. At the same time, the radiographic and functional outcomes of the patients in this study were consistent with previously published studies [ 13 , 16 , 17 ]. When we analyzed the costs of the two groups, we found significant differences.…”
Section: Discussionsupporting
confidence: 91%
“…There was no statistically significant difference in complication rates between the TEN and K wire groups. At the same time, the radiographic and functional outcomes of the patients in this study were consistent with previously published studies [ 13 , 16 , 17 ]. When we analyzed the costs of the two groups, we found significant differences.…”
Section: Discussionsupporting
confidence: 91%
“…Twenty-six case series provided sufficient data regarding angulation at trauma, treatment details, and elbow ROM at follow-up [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The main characteristics of the included studies are listed in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…A higher degree of displacement is usually an indication for surgical treatment[ 3 , 23 , 24 ]. Studies comparing immobilization with percutaneous intervention and percutaneous with open treatment have shown that a conservative approach leads to better outcomes in terms of patient-reported outcome scores, range of motion and fewer complications[ 3 , 4 , 25 ]. However, these results may be confounded by the fact that more severely displaced fractures are often treated more aggressively.…”
Section: Treatment and Outcomementioning
confidence: 99%
“…Open reduction and internal fixation have been associated with a greater loss in range of motion and increased rates of osteonecrosis and synostosis compared to closed reduction techniques[ 3 , 25 , 36 ]. However, these results are controversial due to open reduction being more frequently used in fractures with a higher degree of displacement and more concomitant injuries.…”
Section: Treatment and Outcomementioning
confidence: 99%
See 1 more Smart Citation